Evaluating Automobile Road Vibrations Using BS 6841 and ISO 2631 Comfort Criteria - Nahvi, Hassan; Mohd. Nor, Mohd. Jailani; Fouladi, Mohammad Hosseini; Abdullah, Shahrum (2006)
Evaluation of human exposure whole-body vibration and shock can be carried out in a variety of ways. The most common used standards for predicting discomfort are BS 6841 and ISO 2631 which offer different frequency weightings and multiplying factors to allow for different sensitivity of the body in different axes. For analysis methods based on acceleration, vibration dose value, VDV, gives the highest correlations between vibration magnitude and discomfort. In this study, in order to evaluate vibration characteristics of a passenger car, vibration signals were measured while driving with different speeds over five road surfaces. Accelerations were measured in the vertical, fore-aft, and lateral directions on the seat and fore-aft direction on the seat backrest. Root-mean-square values and power spectral densities of the recorded signals were evaluated to assess transmitted vibrations to the passengers. Results show that generally, vibration level increases as the speed rises. Evaluations according to ISO 2631 give lower VDV values (by about 18%) compared to that of BS 6841.